A general approach to generate Rayleigh fading simulators with correct statistical properties. Issue 5 (15th March 2011) - Yang, Ying; Chen, Xiaohui; Dong, Wenxiang; Wang, Weidong
ABSTRACT Rayleigh fading channel is widely modeled using sum‐of‐sinusoids simulators. In the paper, the construction method of an accuracy simulator is of concern. The intrinsic relationships between path gain, angle of incoming wave (angle of arrival), and initial phase are analyzed. At the same time, rules of simulator construction were proposed. According to these rules, the second‐order statistical properties of designed simulators match to the desired ones perfectly. Furthermore, our method can be an elicitation to generate simulators with correct high‐order statistical properties. In addition, a realization based on the construction method is designed to example how to use these construction rules. The new realization can be used to generate multiple uncorrelated fading waveforms for frequency‐selective fading channels, multiple‐input multiple‐output channels, and diversity combining scenarios. Copyright © 2011 John Wiley & Sons, Ltd.